Reading difficulties encountered by ESL tertiary learners of Pakistan - Abbas, Tarique; Elizabeth M Anthony, (Penerbit Universiti Kebangsaan Malaysia, 2024)
Reading is the core element of language which enhances three remaining skills and one’s familiarity with language knowledge. Reading is a fundamental cognitive skill that plays a pivotal role in developing individuals' intellect, boosting their academic achievements and performance, and parallel lifelong learning skills. This study aims to investigate the reading difficulties faced by undergraduate ESL learners in comprehending textto cull out useful strategies to overcome the reading difficulties. The data for this study was collected from 200 participants using a survey consisting of close-ended questionnaires and was subsequently analyzed using SPSS software. The findings of the present study revealed significant reading difficulties such as lack of vocabulary, weak grammar, difficulty in understanding the sentence structure, and unfamiliarity with technical terms. The findings further revealed that learners frequently employed the following reading strategies to tackle the reading problems: re-reading, translating, and referring to the dictionary. The study highlights the need for targeted interventions in the ESL curriculum to enhance students' reading comprehension by incorporating strategy-based reading instruction, providing access to diverse and engaging reading materials, and offering training in using context for decoding meanings.